Indikator Asam-Basa dari Bunga Dadap Merah (Erythrina crista-galliL.) - Rahmawati, Rahmawati; Nuryanti, Siti; Ratman, Ratman (Universitas Tadulako, 2016)
Dadap red (erythrina crista-galli L.) is belonged to the legumes (fabaceaea) family which, is one of the flowering shade plants that often used as an ornamental plant. This plant has a bright red flower, a taproot with root nodule bacteria nitrogen fixation and compound leaf consists three strands on each stem. This research is climed to proves that the extract of dadap red flower can be used as acid-base indicators. Dadap red flowers was macerated using methanol then filtered. The filtrate was ready to use as an acid-base indicator. The extract is tested in an acid-base, buffer solutions, and was compared with phenolphthalein for a strong acid with a strong base while a methyl orange a weak base with a strong acid. Based on the result, indicator of dadap red flower extrat in the strong acid was red colour, while in the weak acid was pink, and also in the strong base was dark green and in the weak base was purple. Furthermore, in the buffer solution, the indicator of dadap red flower extract gave four groups of colour change, namely red color at pH 1 to pH 6, colorless at pH 7 to pH 9, brown at pH 10 and blue at pH 11 to pH 12. Additionally, to attain the end point of titration, the indicators of dadap red flower extract gives a similar results with the comparison indicators. The results showed that the indicator of dadap red flower extracts can be used as an alternative indicator.